Arabidopsis thaliana. (L.) Heynh Multifunctional Sensor Proteins and Signaling Networks Plant Photoreceptors - R. Ganesh (International Journal of Photochemistry and Photochemical Research, 2024)
Light is a crucial environmental cue for the growth and development of plants as well as the production of photosynthetic energy. In order to recognize and process information from incoming light, plants employ sophisticated mechanisms. With the model plant Arabidopsis thaliana, five different types of photoreceptors have been found. (L.) Heynh Photoreceptors play a specialized and/or recurring role in fine-tuning many aspects of the plant's life cycle. Unlike mobile animals, sedentary plants are highly flexible and can adapt and survive in changing environments. Plants adjust their direction in the right direction by following the different messages created by the light. It is not unexpected that light is connected to plant regulation in many ways, given that variations in the light environment are frequently synchronized with other environmental elements including temperature, abiotic stressors, and seasonal changes. physiology and growth. In fact, recent advances in plant photobiology have revealed large-scale connections between different photoreceptor signaling pathways and other internal systems, such as light Red hormones. In addition, some photoreceptors directly affect the perception of stimuli other than light, such as heat. Therefore, understanding signaling interactions is important for investigating photoreceptor function in plants. Here, we provide an overview of how different photoreceptors work in tandem with internal signals in plants to regulate a range of physiological and biochemical responses. Therefore, understanding the interplay of these interactions is important for studying plant photoreceptor function.
Keywords: E3 Ubiquitin ligase; Photo morphogenesis; Photoreceptors; Sensory proteins; Signal integration